Otomtisasi Perangkat Kelistrikan di Line Produksi Menggunakan Metode PDCA untuk Efisiensi Energi - Junaedi, Putra; Intani, Arvita Emrilis; Wiyatno, Tri Ngudi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Uncontrolled electricity usage in production facilities can lead to significant energy waste and high operational costs. This study designs an automation system to control lighting and ventilation based on work schedules to reduce inefficient energy use. The system is built using Arduino Uno microcontroller and RTC DS3231 module, and the development process is guided by the PDCA (Plan, Do, Check, Act) method to ensure a structured and evaluative approach. The results show that the system successfully reduced electricity usage by 1,991.01 kWh and saved IDR 2,228,854.90 monthly. The PDCA cycle also supported the system's refinement in a measured and gradual manner. This research proves that a simple but well-targeted automation system can significantly contribute to energy efficiency in manufacturing environments.